Nonstandard Version of Intermediate Value Property - Hamad, Ibrahim O.; Hussein, Sami A. (Science Journal of University of Zakho, 2017)
In this paper, some new properties and results about Intermediate Value Property (IVP) via nonstandard concepts are given, and modifying some existing results to show the advantage role of nonstandard analysis tools for obtaining differed nonstandard distinguished results
Keywords: IVP functions; CIVP functions; Functions with perfect road; Bair one functions; monad; s-continuity